A pillar[5]arene-based [2]rotaxane lights up mitochondria - Yu, Guocan (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Subcellular organelle-specific reagents for simultaneous targeting, imaging and treatment are highly desirable for cancer therapy. However, it remains a challenge to fabricate a single molecular platform containing a targeting group, imaging and therapeutic agents through traditional synthesis. Due to their superior sensitivity and photostability, fluorescent probes with aggregation-induced emission (AIE) characteristics have attracted more and more attention in studying the process of translocation, drug release, and excretion of nanomedicines in vitro or in vivo. We construct a pillar[5]arene-based [2]rotaxane (R1) by employing tetraphenylethene (TPE) and triphenylphosphonium (TPP) moieties as stoppers; the TPE unit retains the aggregation-induced emission (AIE) attribute and the TPP group is used as a mitochondria-targeting agent. R1 exhibits enhanced AIE, high specificity to mitochondria, and superior photostability. By introducing doxorubicin (DOX) into R1, prodrug R2 is constructed as a dual-fluorescence-quenched Förster resonance energy transfer (FRET) system, in which the TPE-based axle acts as a donor fluorophore and the DOX unit acts as the acceptor. Upon hydrolysis of R2 in endo/lysosomes, the fluorescences of the carrier and the drug recover. R1 is further utilized as a drug delivery platform to conjugate other anticancer drugs containing amine groups through imine formation to prepare prodrugs. The anticancer drugs are released from these prodrugs in the cells upon hydrolysis of the pH-responsive imine bonds.